A Reply to Elena Kagan Can't Say That: The Sorry State of Public Discourse Regarding Constitutional Interpretation - Eric J. Segall (Washington University Law Review, 2010)
Written in the form of a fictional memo by Elena Kagan to the President of the U.S., this commentary offers a reply to the fictional memo by the President’s Counsel arguing that the President should not allow Justice Kagan to proceed with her remarks. The memo concedes the Counsel’s view that conservatives have succeeded in establishing the view that there are two types of judges: the liberal, activist and the conservative judge. The memo argues that Justice Kagan’s statement would offer a persuasive case against the conservative agenda, suggesting that neither the left nor the right has a monopoly on judicial activism. The proposed reply makes the case that charges of judicial activism fallaciously distract from the question of whether or not the American people agree with judicial decisions. Finally, the reply counters the objections of the Counsel concerning strategy by suggesting that media attention will offer a chance for persuasive dialogue as opposed to an embittered nomination fight.
Keywords: Judges -- Selection & appointment; Political questions & judicial power; Kagan; Elena; 1960-